Noun–verb naming dissociation in neurosurgical patients. Issue 12 (2nd December 2019) - Tomasino, Barbara; Tronchin, Giulia; Marin, Dario; Maieron, Marta; Fabbro, Franco; Cubelli, Roberto; Skrap, Miran; Luzzatti, Claudio
ABSTRACT: Background : Dissociated impairment of noun and verb retrieval has been frequently reported after vascular brain lesions: selective damage of either grammatical class allowed to test models of lexical processing and of its neuroanatomical foundation. However, vascular lesions are often quite large and do not involve brain structures uniformly. Neurosurgical lesions do not undergo such apparent limitation, being usually smaller and better distributed across the cerebral cortex. Aims : We explored the neuroanatomical correlates of noun–verb naming processing and dissociations by means of the voxel-based lesion symptom mapping (VLSM) procedure and the subtraction of lesion volume of interests (VOIs) approach in a series of 99 neurosurgical patients. Methods and Procedures : The VOIs and behavioral data for noun and verb naming were analyzed in a VLSM procedure. The verb (or noun) naming performance was included as a covariate control variable, which allowed testing effects on noun (or verb) naming, controlling for the verb (or noun) naming performance. The total lesion volume was also included as a covariate to avoid spurious effects. Outcomes and Results : Eighteen patients showed a significant dissociation between noun and verb naming: seven patients showed disproportionate impairment in naming nouns, and eleven patients with disproportionate impairment in naming verbs. In addition, there were 27 undifferentiated patients, i.e. performing abnormally on nouns and/or verbs, but non-dissociating between the two word classes.VLSM in combination with the subtraction of lesion mask analyses revealed that verb naming impairments were related with lesions in the middle frontal gyrus, precentral gyrus, parietal and rolandic operculum, supplementary motor area, and the inferior parietal (supramarginal and angular gyri), whereas noun naming impairments were associated with basal temporo-occipital lesions. Furthermore, data indicate that noun and verb naming deficits also depend on a disconnection phenomenon: at subcortical level, noun naming impairments are related to damage to parts of the sagittal stratum (including the inferior fronto-occipital fasciculus and the inferior longitudinal fasciculus), the splenium of the corpus callosum, the posterior thalamic radiations (plus optic radiations), the retrorolandic part of the internal capsule, the tapetum and the fornix. On the contrary, verb naming impairments are related to damage to parts of the superior and posterior corona radiata, and of the anterior and posterior limb of the internal capsule. Conclusions : Summing up, results point to verb-specific areas in the superior frontal as well as the inferior parietal cortex, and noun-specific basal temporo-occipital and subcortical neural circuitries.